3D Photoelectron Velocity Map Imaging and Four-Wave Mixing of Cylindrical Vector Modes - Goudreau, Edward Scott (Université d'Ottawa / University of Ottawa, 2025)
The 2D photoelectron velocity map imaging (VMI) technique is commonly employed in gas-phase molecular spectroscopy and dynamics investigations due to its ability to efficiently extract photoelectron spectra and angular distributions in a single experiment. However, the standard technique is restricted to specific light-source polarization geometries by the need to perform a mathematical inversion of the measured 2D detector-plane projections in order to recover the spherical 3D particle distribution. This has led to significant interest in the development of 3D VMI techniques which are capable of measuring, at a detector, the transverse position (x, y) and time-of-flight (TOF, t) of individual events in order to obtain a full set of 3D coordinates, thus avoiding the need for inversion and the associated constraints. These techniques employ curved velocity-mapping electric field lines, making the general transformation of (x, y, t)-data into initial 3D recoil momentum vectors (p_x, p_y, p_z) a challenging problem which, until now, was not fully addressed. Here I present and demonstrate a novel time-stretched, 13-lens 3D VMI photoelectron spectrometer which has sub-camera-pixel spatial resolution and 72 ps (σ) TOF resolution. This instrument employs a kHz CMOS camera to image a standard 40 mm diameter microchannel plate (MCP)/phosphor anode detector (providing x and y positions), combined with a digitizer pickoff from the phosphor to obtain the electron TOF. This thesis contains my work on testing and evaluating the performance of this spectrometer, as well as developing a complete data processing and analysis protocol to convert raw 3D VMI data (camera images and digitizer waveforms) into 3D charged particle recoil momentum vectors. I demonstrate the advantages of the 13-element design, showing that the greater spread in electron TOF permits an accurate time- and position-stamping of up to six electrons per laser shot at a 1 kHz repetition rate. In a second project, I develop a theoretical description of the nonlinear optical process of four-wave mixing (FWM) as it applies to a type of structured light mode called cylindrical vector (CV) beams. The CV modes are eigenmodes of optical fibre and, as such, they have a broad range of application, such as telecommunications, quantum cryptography, and fundamental optics research. Despite this, their nonlinear optical properties are not yet well understood. Here I derive the selection rules which determine the allowed FWM processes involving CV modes in optical fibre.
Keywords: Velocity Map Imaging; Photoelectron Angular Distributions; Photoelectron Spectroscopy; Charged Particle Imaging; Nitric Oxide; Four-Wave Mixing; Structured Light; Cylindrical Vector Modes; Nonlinear Optics